SOCIAL-PHILOSOPHICAL ASPECTS OF MANAGEMENT ACTIVITIES: A RELATIONAL APPROACH (TAMADDUN NURI JURNALI, 2025)
This paper explores the intersection of social philosophy and management, emphasizing a relational approach. It examines how philosophical principles inform management practices, focusing on human relations, ethical considerations, and the cultivation of social capital within organizations. Through a comprehensive literature review and theoretical analysis, the study highlights the importance of integrating philosophical values into management to enhance organizational effectiveness and employee well-being. The social-philosophical aspects of management activities emphasize the intricate relationships between individuals, organizations, and society. A relational approach to management highlights the significance of social interactions, ethical considerations, and cultural contexts in decision-making and organizational structures.